Herds of Featherless Bipeds: Division and Privation in Plato’s Statesman (Revista Archai, 2025)
This paper explores privation in the Statesman, first from a methodological point of view, and then politically. I begin (§1) with the Rule of Bisection (262a-e): classes should be bifurcated by form, which apparently excludes division by positive and negative terms (e.g. human and non-human). The significance of the restriction is debated. I argue that the correct interpretation must take into account the preponderance of privative terms in the subsequent divisions of animals. According to one definition, humans are two-footed, non-interbreeding, hornless land animals; according to another, they are featherless, two-footed land animals (264d-266e). On my reading of the rule, classes should be bifurcated with reference to constitutive features of the resulting subclasses; while negative properties never satisfy this requirement, privations are in some cases partly constitutive of the target class in division. This insight allows me to offer a charitable reading of the Eleatic Stranger’s definitions of the human herd, which others have disparaged, as relevant for political theory (§2) and tightly linked with the Myth of the Ages (268e-274d) that follows these divisions (§3). In the final section, I sketch a unified outlook on the dialogue as concerned with effective political collaboration, under the supervision of a statesman who expertly integrates each member into the self-protective fabric of society (§4).